Understanding Network Congestion Effects On Performance: Article Review - Mohamed, N. J.; Sahib, Shahrin; Suryana, Nanna; Hussin, Burairah (JATIT & LLS, 2016)
Networking communications have become popular worldwide in human daily services. Network Congestion (NC) happens whenever because nodes and links are overloaded. Such situations affect the network expected performance and its services quality. Congestion /NC occurs as a results of its subnets’ links overload, which gradually (overtime) affects the network performance with an increase of transmission delay, a slowdown of throughput as generally perceived by network’s users. NC is considerable as the basis problem in network performance quality acceptance; and most of its existing problem solutions are expected still playing a great role in the future networks model, which will be running mostly too many multimedia applications. However, various researches over past years have initiated the study on the causes leading to congestion and, different lessons can be learnt from NC situations analysis to understand its relationship with the future network’s performance. This paper presents an analytical review of NC occurrence causes and the fundamentals of the existing control solutions/frameworks as available and studied from some former and recent networks publications. A particular attention has been paid throughout this study to found out how NC may still affect the future networks performance (i.e. QoS in the world of multimedia networks). And the coverage/content of this paper is expected to serve as a quick access to the knowledge essentials for researchers on related subject as stated in this paper topic.